Treatment of posttransplant lymphoproliferative disorder with poor prognostic features in children and young adults: Short‐course EPOCH regimens are safe and effective. Issue 8 (21st May 2021) - Rubinstein, Jeremy D.; Shah, Rachana; Breese, Erin H.; Burns, Karen C.; Mangino, Jennifer L.; Norris, Robin E.; Lee, Lynn; Mizukawa, Benjamin; O'Brien, Maureen M.; Phillips, Christine L.; Perentesis, John P.; Pommert, Lauren; et al.
Abstract: No guidelines exist for which intensive chemotherapy regimen is best in pediatric or young adult patients with high‐risk posttransplant lymphoproliferative disorder (PTLD). We retrospectively reviewed patients with PTLD who received interval‐compressed short‐course etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin (SC‐EPOCH) regimens at our institution. Eight patients were included with median age of 12 years. All patients achieved a complete response with a manageable toxicity profile. Two patients developed second, clonally unrelated, EBV‐positive PTLD and one patient had recurrence at 6 months off therapy. No graft rejection occurred during therapy. All eight patients are alive with median follow‐up of 29 months.